The Qur'anic Foundation of Love-Based Curriculum (KBC): An Analysis of Thematic Interpretation of Humanistic Islamic Education - Alfian Dhany Misbakhuddin; Abd. Muqit; Ratna Etikasari Agus; Ahda Sabiela; Medina Nur Asyifah Purnama (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examines the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) developed by the Indonesian Ministry of Religious Affairs from a Qur’anic perspective. The research analyzes the Qur’anic normative foundations of the values of love that underpin the curriculum and their relevance to the development of humanistic Islamic education. This study employs a qualitative-descriptive approach, drawing on library research. Primary data were derived from the Qur’an, classical and contemporary tafsir literature, and official documents of the Love-Based Curriculum issued by the Ministry of Religious Affairs. The data were analyzed using the thematic interpretation method (tafsīr mawḍū‘ī), focusing on Qur’anic verses related to love, compassion, humanity, knowledge, and the environment. The findings reveal that the Love-Based Curriculum possesses a strong normative foundation in the Qur’an. Love for Allah and the Prophet serves as the spiritual foundation of education, while love for fellow human beings emphasizes the importance of inclusive, tolerant, and humanistic education. Furthermore, love for knowledge positions education as a means of intellectual and moral transformation, whereas love for the environment reflects the eco-theological dimension of Islamic education. This study concludes that the Love-Based Curriculum is not merely a pedagogical innovation, but also an actualization of Qur’anic values within contemporary Islamic education. Therefore, the curriculum may serve as a paradigm of humanistic Islamic education that integrates spirituality, morality, intellectuality, and socio-ecological awareness in shaping holistic human beings.